Adsorption Kinetics of Toxic Heavy Metal Ions from Aqueous Solutions onto Grafted Jute Fibers with Acrylic Acid by Gamma Irradiation - Mahmoud S. Hassan; Maged H. Zohdy (Journal of Natural Fibers, 2018)
Jute fibers were used as an adsorbent substrate for Hg2+ and Pb2+ metal ions as toxic pollutants from their aqueous solutions after graft copolymerization with polyacrylic acid under the effect of gamma irradiation. The treated jute fibers were characterized by using of Fourier-Transform Infrared Spectroscopy. The effects of solution pH, contact time, temperature, and the dissolved metal ions’ concentration on the adsorption efficiency were investigated. The adsorption kinetics and the used adsorption isotherm were also investigated. From the results, it was concluded that the adsorption process conformed the second-order kinetic reaction and followed the Langmuir adsorption isotherm model, and the higher adsorption capacities were at pH 5 and 6 for Pb2+ and Hg2+ metal ions respectively.